2021
DOI: 10.30935/scimath/11382
|View full text |Cite
|
Sign up to set email alerts
|

HOTS in Quadratic Equations: Teaching Style Preferences and Challenges Faced by Malaysian Teachers

Abstract: The purpose of this study is to identify the teaching styles and problems faced by teachers as they attempt to cultivate higher-order thinking skills (HOTS) in the topic of quadratic equations. This study used a qualitative approach via structured interview involving four participants who are experienced mathematics teachers from three districts in Malaysia. Data obtained were analysed using the ATLAS.ti 8 software by dividing the transcripts into small codes based on thematic analysis. The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Quadratic equation is a compulsory and important topic to be learned in secondary school mathematics as it bridges the gap between functions, polynomial derivatives, and linear equations (Kim How et al, 2022). Kim How et al (2022) argue that besides connecting with linear equations, QE is a vital branch of mathematics that is applicable in solving problems in engineering and structural design, physics, as well as in real-life modelling and word problems. According to Yeow et al (2019), QE seems to be an easy topic to learn which involves basic skills that can be applied in sports and architecture.…”
Section: Errors In Learning Mathematicsmentioning
confidence: 99%
“…Quadratic equation is a compulsory and important topic to be learned in secondary school mathematics as it bridges the gap between functions, polynomial derivatives, and linear equations (Kim How et al, 2022). Kim How et al (2022) argue that besides connecting with linear equations, QE is a vital branch of mathematics that is applicable in solving problems in engineering and structural design, physics, as well as in real-life modelling and word problems. According to Yeow et al (2019), QE seems to be an easy topic to learn which involves basic skills that can be applied in sports and architecture.…”
Section: Errors In Learning Mathematicsmentioning
confidence: 99%
“…Studies have demonstrated that most learners struggle with QE (Kim How et al, 2022;Makgakga, 2016;Tendere & Mutambara, 2020). Tendere and Mutambara (2020) point out that most learners appear to experience difficulties in solving QE by both factoring and using quadratic formula methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quadratic equations are a branch of mathematics that cut across all spheres and that need to be taught and learned in secondary schools (Cahyani & Rahaju, 2019). Quadratic equations is a compulsory and important topic to be learned in secondary school mathematics as it bridges the gap between functions, polynomial derivatives, and linear equations (Kim How et al, 2022). Kim How et al (2022) argue that besides connecting with linear equations, QE is a vital branch of mathematics that is applicable in solving problems in engineering and structural design, physics, as well as in real-life modelling and word problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of teaching and learning modules is one of the suitable strategies employed to achieve this goal. Previous research has shown that using modules in the teaching and learning process can benefit students of all abilities [2]. Additionally, modules can help students solve chemistry problems more effectively and connect newly learned theory to existing insight, which can assist them in learning [3].…”
Section: Introductionmentioning
confidence: 99%